Effects of public expenditure assignment by regions in Kazakhstan to reduce infant and child mortality - Yolanda Pena-Boquete; Aizhan Samambayeva; Olzhas Zhorayev (Cogent Economics & Finance)
Health resources are an important factor to reduce infant and child mortality. However, taking into account budget constraints, it is very difficult to increase public health resources for all regions within a country at the same time. For this reason, in this paper, we assess the effects of the regional health government expenditure assignment as well as the regional health resources available such as beds or paediatricians. We estimate a dynamic model using a system-GMM (Generalised Method of Moments) to explain infant and child-mortality in Kazakhstan during the period 2000–2018. In this period, Kazakhstan experiences a sharp decrease in infant and child mortality reaching the target values from sustainable development goals (SDG). We evaluate several variables to capture the effects of public health resources assignment, such as expenditure per capita, expenditure depending on previous year mortality rates as well as health facilities resources for children by region. Results show that an increase in health expenditure per capita in those regions with high mortality levels is particularly relevant to reduce infant mortality while health facilities are actually more important to reduce an under-5 mortality rate.